2009
DOI: 10.1667/rr1607.1
|View full text |Cite
|
Sign up to set email alerts
|

A Nested Case-Control Study of Multiple Myeloma Risk and Uranium Exposure among Workers at the Oak Ridge Gaseous Diffusion Plant

Abstract: The primary risk factors of multiple myeloma are age, race and sex, but several studies have found an association between radiological hazards and multiple myeloma. The purpose of this nested case-control study was to investigate whether workers with chronic low-level exposure to internally deposited uranium at the Oak Ridge Gaseous Diffusion Plant in eastern Tennessee were at higher risk of dying of multiple myeloma than those without occupational exposure to uranium, with the consideration of potential confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…Age and race are considered as risk factors for multiple myeloma. Exposure to radiation and occupational exposures to high levels of benzene or formaldehyde are considered as risk factors for both multiple myeloma and leukemia (Romanenko et al, 2008;Yiin et al, 2009;Rhomberg et al, 2011).…”
Section: Epidemiology Of Leukemia and Multiple Myeloma In Golestanmentioning
confidence: 99%
“…Age and race are considered as risk factors for multiple myeloma. Exposure to radiation and occupational exposures to high levels of benzene or formaldehyde are considered as risk factors for both multiple myeloma and leukemia (Romanenko et al, 2008;Yiin et al, 2009;Rhomberg et al, 2011).…”
Section: Epidemiology Of Leukemia and Multiple Myeloma In Golestanmentioning
confidence: 99%
“…Similar results were reported among Sellafield workers [31], where a statistically significant trend with external radiation exposure among plutonium workers was observed in comparison with non-radiation exposed workers. Several studies on uranium workers reported an increase in mortality due to lymphatic or hematopoietic malignancies [36][37][38][39][40][41][42][43][44][45][46] but only a few of them investigated the relationship with uranium internal exposure [38,[45][46][47][48]. Ritz et al [46] observed a positive association (trend) between internal radiation dose and risk of mortality from lymphatic and hematopoietic malignancies in the Rocketdyne plant worker cohort.…”
Section: Consistency With Epidemiological Datamentioning
confidence: 99%
“…Their doseresponse analyses showed that the second (21-50 lg y) and third (51-125 lg y) quartiles of internal uranium exposure were significantly elevated for NHL (RR = 9.95 (95% CI: 1.22-81.26) and RR = 8.85 (95% CI: 1.11-70.88), respectively) while the fourth quartile ([125 lg y) was non-significantly elevated (RR = 5.74 95% CI: 0.72-45.48) [47]. Lastly, a nested case-control study of multiple myeloma (MM) conducted among workers at the Oak Ridge gaseous diffusion plant [48] found that the risk of MM increases with increasing internal uranium dose to red bone marrow. The risk was 1.04 (95% CI: 1.00-1.09) at 10 lGy after accounting for age, race, sex, and occupational chemicals, such as mercury, nickel, and TCE [48].…”
Section: Consistency With Epidemiological Datamentioning
confidence: 99%
“…Nevertheless, most studies conducted up to now were limited in their capacity to demonstrate an associated risk, mainly due to their reduced statistical power or to the poor quality of their dosimetric data (Guseva Canu et al, 2008a). However, new studies have been recently launched in the US based on updated cohorts with comprehensive exposure assessment and internal dose estimation and have already provided informative results with respect to the lymphatic and haematopoietic tissue malignancies (Yiin et al, 2009;Chan et al, 2010;Boice et al, 2011). In Europe, a similar study was conducted in France, in the framework of a pilot investigation; though internal doses have been only partially assessed.…”
Section: Epidemiological Issuesmentioning
confidence: 99%